Financial Development, the Structure of Capital Markets, and the Global Digital Divide - Yartey, Charles Amo (IMF Working Papers; Working Paper ;, 2006)
This paper examines the role of financial development and financial structure in explaining cross-country diffusion of information communication technology (ICT). Using panel data for 76 emerging and advanced countries for the period 1990-2003, the paper finds that credit and stock market development tends to foster ICT development. Financial structure, however, does not appear to have any significant relationship with ICT development. The conclusions of the paper highlight the role of financial development in the market for knowledge-based products, and are consistent with theoretical predictions. The finding that financial development is an important determinant of ICT development implies that countries with underdeveloped financial markets may continue to lag behind in the use of ICT.